IMPLEMENTASI PENDIDIKAN HAK ASASI MANUSIA DALAM KURIKULUM SEKOLAH DI NUSA TENGGARA TIMUR: TANTANGAN DAN PELUANG : Penelitian ini menerapkan pendekatan deskriptif kualitatif - Sesilia Ruron; yoriana Atti; Theresia B. S. Keransj; Yeremia Kabnani; Fadil Mas'ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Human Rights Education (HRE) plays an important role in shaping learners who are civilized and uphold human dignity. In Indonesia, its implementation is grounded in Law Number 20 of 2003 on the National Education System and the National Human Rights Action Plan (RANHAM) 2021–2025. However, the practice of HRE continues to face obstacles, particularly in diverse regions such as East Nusa Tenggara (NTT), where public awareness of human rights values remains low (Wulandari, 2022). Challenges also appear in the areas of educational equity and teacher quality, with the average length of schooling at only 7.63 years and certified teachers reaching just 22% (Statistics Indonesia, 2023b; Ministry of Education, 2024; Ombudsman of the Republic of Indonesia, 2023c). Moreover, early school start-time policies have been criticized as inconsistent with children's rights principles (National Human Rights Commission, 2023). Other barriers include limited resources, weak local policies, and insufficient integration of human rights values into the curriculum (Darmawan & Rante, 2023; Suharto, 2021). Nevertheless, the Merdeka Curriculum offers opportunities to strengthen character and human values through the Pancasila Student Profile (Ministry of Education, 2022). This study examines the implementation, challenges, and opportunities of HRE in schools across NTT as a foundation for developing humanistic and inclusive policies.